TanDEM-X & Tandem-L: Setting Benchmarks in Radar Remote Sensing - Krieger, Gerhard; et al. (International Astronautical Congress (IAC), 2018)
The operation of two SAR satellites flying in close formation enables bistatic operation allowing for highly accurate single-pass interferometry. TanDEM-X has been operationally demonstrating this novel technique since 2010. With a typical separation between the TerraSAR-X and TanDEM-X satellites of 120 to 500 m a global DEM with 1 m height accuracy at 12 m posting has been generated. Final DEMs are of consistent homogeneous quality and well within specifications. Tandem-L, a proposal for an innovative L-band SAR mission, is also employing bistatic interferometry aiming at the systematic observation of dynamic processes on the Earth's surface. Thanks to the novel imaging techniques and the vast recording capacity of up to 8 Terabytes/day, it will provide vital information for solving pressing scientific questions in the biosphere, geosphere, cryosphere, and hydrosphere and will make an essential contribution for a better understanding of the Earth system and its dynamics.
Keywords: close formation flight; bistatic SAR; single-pass interferometry; TanDEM-X; Tandem-L